THE EFFECTIVENESS OF THE CIRCUIT-BASED FUTSAL LEARNING MODEL ON FUTSAL PASSING AND CONTROL SKILLS - Wenly, Ayu Purnama; Pelana, Ramdan; Sulaiman, Iman; Nasution, Harry Syahputra (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2025)
This study aimed to determine the effectiveness of a circuit-based futsal learning model in improving passing and ball control skills among university students. The research employed a pre-experimental one group pre-test post-test design. The sample consisted of 30 students selected through purposive sampling. The instruments used were a futsal passing test and a ball control test, both validated by experts. The intervention was conducted over [ 16 /weeks], implementing circuit training focused on mastering passing techniques and ball control in game-like situations. Data analysis employed a paired sample t-test with a 0.05 significance level and effect size calculation (Cohen’s d). The results indicated an increase in the mean score from 36.57 in the pre-test to 44.93 in the post-test, with a p-value = 0.000 (<0.05) and Cohen’s d = 4.58 (very large effect). These findings demonstrate that the circuit-based learning model is highly effective in enhancing fundamental futsal skills, particularly passing and ball control, making it a strong recommendation for application in both academic settings and competitive training environments .